Pemberdayaan Kemampuan Literasi Sains melalui Model SSCS terintegrasi Strategi RQA - Yusnaeni; Imakulata, Mbing. M.; Nikmah; Santrum, Mario. J.; Jasman; Sudirman; Dama, Waldetrudis. V.; Bangngu, Nolvan. C.; Wiltin, Gabriela. F.; Tukan, Etheldrida S. T. (Universitas Negeri Jakarta, 2024)
Understanding science is needed in the context of scientific literacy. Scientific literacy cannot be separated from the role of reading literacy. Literacy is a prerequisite component so that students can have four life competencies namely Creativity, Critical Thinking, Collaboration, and Communication (4C). This research is quasi-experimental research with a pretest and post-test non-equivalent control group design. The population is students from SMP Negeri 9 and 17 with a class VIII sample of 105 students. The instrument for assessing students' scientific literacy skills is in the form of multiple-choice tests and essays prepared to represent indicators of scientific literacy, namely: 1) identifying scientific problems/phenomena, 2) interpreting data and drawing conclusions, 3) understanding science concepts, and 4) applying science concepts to life. Data on students' scientific literacy abilities analyzed using the t-test. using the SPSS ver. 20. The research results obtained show that there is a difference in scientific literacy between the SSCS model treatment group integrated with RQA learning strategies and the conventional model. The SSCS+RQA class experienced an increase of 52.48%. The significant increase changed the scientific literacy category from low to very high. Meanwhile, the RQA control class experienced an increase of 33.89%. This increase was also able to change the scientific literacy category from low to high.